Pricing policy of a construction and manufacturing enterprise and its impact on competitiveness - O.S. (Економіка, управління та адміністрування, 2023)
Today puts entrepreneurial activity in the framework of fierce competition, which becomes a determining factor in the way of pricing products of construction and manufacturing enterprises. Establishing a reasonable level of prices in the market of building materials is one of the main objective factors influencing the successful planning of the work of organizations, which includes forecasting the effectiveness of pricing policy and understanding the extent to which the planned pricing system will solve the possibility of successful development and opposition to competitive policy. The article introduces the method of creating a price policy of construction and manufacturing enterprises, the main goals and objectives are established. The need for a preliminary assessment of the demand for this group of goods to achieve the desired financial result was revealed. Within the framework of this scientific study, the project is presented to create a construction material costing, taking into account all components of the production cost. The importance of the influence of the market policy of competitors on the pricing of one's own range of goods is substantiated. Factors and pricing methods are considered. Special attention is focused on determining the final price of products.